2022
DOI: 10.1111/jfb.15047
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic behaviour of wild eels and depressed survival and growth of farmed eels in mixed rearing experiments

Abstract: To contribute to improving eel stocking procedures, the survival, growth and behaviour of farmed Japanese eels reared together with wild individuals were evaluated to learn about possible encounters of farmed‐ and stocked eels with wild eels. Two experiments were conducted to evaluate the (a) effect of the presence of wild eels on survival and growth of farmed eels in experimental ponds and (b) behavioural differences between wild and farmed eels placed in a small tank. In the survival and growth experiment, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Based on a mixed rearing experiment, Wakiya et al . (2022) reported that the growth rate of farmed Japanese eels is reduced when they are reared with wild eels, corresponding to the results obtained in this study. Therefore, wild eels in recipient water bodies likely interfere with the growth of farmed Japanese eels stocked there.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Based on a mixed rearing experiment, Wakiya et al . (2022) reported that the growth rate of farmed Japanese eels is reduced when they are reared with wild eels, corresponding to the results obtained in this study. Therefore, wild eels in recipient water bodies likely interfere with the growth of farmed Japanese eels stocked there.…”
Section: Discussionsupporting
confidence: 89%
“…Wakiya et al . (2022) also observed reduced survival and growth rates of farmed eels when they were reared with wild eels for 2 years with live food (freshwater shrimp), whereas farmed eels showed similar survival and growth rates compared to wild eels when they were reared without wild eels. That study indicated that wild eels might be more competitive than farmed‐and‐stocked eels and they might interfere with the survival and growth of stocked eels through intraspecific competition.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations